2016
DOI: 10.1080/15476278.2016.1194148
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C promotes the proliferation of human adipose-derived stem cells via p53-p21 pathway

Abstract: ABSTRACT. Although adipose-derived stem cells (ADSCs) have demonstrated a promising potential for the applications of cell-based therapy and regenerative medicine, excessive reactive oxygen species (ROS) are harmful to ADSCs cell survival and proliferation. Vitamin C is an important antioxidant, and is often added into culture media as an essential micronutrient. However, its roles on the proliferation of human ADSCs have not been studied. Therefore, in this study, human ADSCs were isolated, and detected by fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…1). In accordance with previous studies, VC treatment was demonstrated to increase the proliferation rate in various kinds of mesenchymal stem cells [29,32]. VPA was reported to accelerate the proliferation and differentiation of neural stem cells but inhibit the propagation of mesenchymal stem cells and epithelial cells [33][34][35].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…1). In accordance with previous studies, VC treatment was demonstrated to increase the proliferation rate in various kinds of mesenchymal stem cells [29,32]. VPA was reported to accelerate the proliferation and differentiation of neural stem cells but inhibit the propagation of mesenchymal stem cells and epithelial cells [33][34][35].…”
Section: Discussionsupporting
confidence: 88%
“…2c). Previous studies indicated that VC promoted the cell cycle by upregulating cyclin E1 and CDK2 and downregulating p53 and p21 [32]. The life span and telomere expression of hAECs was extended by 50 μg/ml VC (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…Perioperative topical ascorbic acid (AA) has been shown preventive effects of corneal endothelial dysfunction in high-risk patients undergoing phacoemulsification [16]. AA has shown promoting proliferation effects in other human cells [25,26]. In vitro evidence also shed light on the proliferative effects of AA on corneal endothelial cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…At D4, paraxial mesoderm-like precursors became brown adipocyte precursor cells upon treatment for 48h with insulin, FGF2, Chiron, and LDN-193189 (a BMP inhibitor). Also, ascorbic acid was used to promote proliferation 26 . Following adipocyte precursor formation, the cells were treated with adipogenic induction between D6-D8, requiring culturing cells in DMEM/HAMF12 medium supplemented with triiodothyronine (T3), dexamethasone, 3-isobutyl-1-methylxanthine (IBMX), biotin, pantothenate, insulin, rosiglitazone, ascorbic acid and serum.…”
Section: Resultsmentioning
confidence: 99%